(untitled) (Res Medica, 2014)
Throughout its history the Royal Medical Society has striven to be a forum for debate, allowing the presentation of new and challenging ideas as well as critically reviewing the old. It is hoped that RES MEDICA embodies these principles in a balanced manner. Medicine and the media have come to blows on many subjects in the past, but the last year was notorious in every respect. Technological wizardry wielded by some misinformed pedant brought visions of death, disorder and disability into peoples’ homes. The controversy surrounding brain death was damaging enough to both patients and doctors, but this was followed by a series of documentaries about decisions on whether to allow ’severely’ handicapped neonates to live. One hopes that the current trial of a paediatrician in England will not set a precedent. The attitudes towards handicapped children have changed dramatically in the last few years, and Dr. Raeburn in his article "Active Management in Serious Genetic Disorders" should provoke some fresh thoughts on patients previously considered to be without hope. Civil disorder is only too well known to all of us and the distressing increase in apparently motiveless brutality in our society — particularly towards the elderly — makes Prof. MacLennan’s article "Muggings and Assault" cogent reading. The disabled suffer not only from pain but also immobility in many cases and the advances in joint prostheses offer hope to those with degenerative joint disease especially. These advances have been paralleled with better understanding of clinical methods and ’investigations. Mr. Macnicol admirably outlines these in "The Diagnosis of Knee Pain".